Sex-related inequalities in current cigarette smoking among adolescents in Africa - Richard Gyan Aboagye; Aliu Mohammed; Precious Adade Duodu; Qorinah Estiningtyas Sakilah Adnani; Abdul-Aziz Seidu; Bright Opoku Ahinkorah (BMC, 2024)
Abstract Introduction Risky behaviours, including tobacco use, are highly prevalent among adolescents worldwide. Although these behaviours are largely influenced by various sociodemographic factors, including sex, there is a paucity of regionally representative literature on the sex-related inequalities in cigarette smoking among adolescents in Africa. This study examined the sex-based disparities in current cigarette smoking among adolescents aged 13-15 years in Africa. Methods The present study employed a secondary analysis of nationally representative data on 45 African countries obtained from the Global Youth Tobacco Survey, accessible through the World Health Organization (WHO) Global Health Observatory. We used the online version of the WHO Health Equity Assessment Toolkit (HEAT) to generate the results. Results The prevalence of current cigarette smoking among the adolescents surveyed ranged from 1.6% in Eritrea to 10.4% in Mali among the low-income countries, from 1.3% in Tanzania to 13.1% in Mauritania among the lower-middle-income countries, from 5.2% in Gabon to 15.3% in Mauritius among the upper-middle-income countries, and 14.7% in Seychelles, the only high-income country in the study. The absolute summary measure (D) showed diverse sex-related disparities in the burden of current cigarette smoking among adolescents across the sub-regions. In all countries surveyed, the prevalence of cigarette smoking was higher among male adolescents compared to females, except in Liberia and Mozambique, where female adolescents bore a more significant burden than their male counterparts. Furthermore, male adolescents were more burdened with high cigarette smoking prevalence than females in low-income countries such as Mali, Madagascar, Guinea, Burkina Faso, and The Gambia, where such disparities were most pronounced. Meanwhile, we found less disparity in the burden of cigarette smoking between male and female adolescents in most of the lower and upper-middle-income countries surveyed. Conclusion This study sheds light on the sex-based inequalities in the prevalence of current cigarette smoking among adolescents in Africa. In contrast to female adolescents, male adolescents bear a greater burden of current cigarette smoking. The burden of cigarette smoking is most pronounced in low-income countries such as Mali, Madagascar, Guinea, Burkina Faso, and The Gambia. Conversely, in most of the lower and upper-middle-income countries surveyed, the burdens of current cigarette smoking among male and female adolescents were found to be less disparate. Consequently, cigarette smoking prevention programmes and strategies must be implemented in all African nations. There is also the need to intensify interventions aimed at altering the smoking behaviour of male adolescents. Policymakers can develop and implement evidence-based interventions to address the burden of cigarette smoking among the adolescents. Finally, existing policies and programmes addressing adolescents' cigarette smoking should be re-assessed and strengthened to achieve their objectives.